Implementation of the Free Nutritious Meal Program in Indonesia: A Systematic Review of Governance, Institutional Capacity, and Implementation Gaps - Muh. Firyal Akbar (International Journal Papier Public Review, 2026)
The Free Nutritious Meal (MBG) Program is a national strategic policy that integrates nutrition fulfillment, education, social protection, and human resource development agendas. However, Indonesia’s scale and territorial heterogeneity create implementation challenges that cannot be explained solely through distribution achievements or nutritional outcomes. This study aims to synthesize scientific evidence on MBG implementation from a public policy perspective by examining gaps between policy design and practice, institutional capacity, inter-actor governance, local adaptation, and implementation fidelity. The study employs a systematic review guided by PRISMA 2020, with literature searches conducted through Scopus, Web of Science, PubMed/MEDLINE, Crossref, and OpenAlex. Eligible studies were analyzed using narrative thematic synthesis with a deductive-inductive approach. The synthesis shows that MBG implementation does not follow a uniform pattern. The ability of Nutrition Fulfillment Service Units (Satuan Pelayanan Pemenuhan Gizi, SPPG), implementer competence, facility and logistics readiness, food safety, multilevel coordination, and the capacity to modify national standards to local conditions all play a role in the success of implementation. However, regulatory clarity and resource support are crucial foundations. When coverage growth is not followed by corresponding operational capacity, supervision, and policy-learning processes, gaps between policy-as-designed and policy-as-implemented occur. Policy design → implementation capacity → inter-actor governance → local adaptation → implementation fidelity → program outcomes are all positioned as interrelated mechanisms in this review's synthesis model. Therefore, a change from an expansion- and output-oriented strategy to adaptive governance that strikes a balance between standardization, local capacity, equity, food safety, accountability, and outcome-based monitoring is necessary for the sustainability of MBG.